The effect of applicant’s impression management strategies on personality rating in interview - Park, SoHyun; Yoo, TaeYong (Korean Journal of Industrial and Organizational Psychology, 2014)
The purpose of this study was to examine the influence of impression management strategies on Big 5 personality rating in interview. We made up four different videos that the same hypothetical applicant used different impression management strategies during the three minutes interview. The hypothetical applicant used a combination of the assertive strategy(high versus low) and non-verbal strategy(use versus no-use). The sixty-eight raters evaluated Big 5 personality traits of the applicant after they watched one of four videos(2 × 2 experimental conditions). It was found that the raters evaluated the applicant’s emotional stability and openness were high when the applicant used high assertive strategy than low assertive strategy. Also, the raters evaluated the applicant was more extroverted, agreeable, conscientious, emotionally stable, open when the applicant used non-verbal strategy(such as eye-contact, smiling, and nodding) than not used. In addition, interaction effect between the assertive strategy(high versus low) and non-verbal strategy(use versus no-use) was found in the rating of emotional stability. Specifically, the simple main effect of assertive strategy was not strong when the applicant used non-verbal strategy. But the rater evaluated the applicant was more emotionally stable in high assertive strategy condition than low assertive strategy condition when the applicant not used non-verbal strategy. Finally, theoretical and practical implications, limitations of this study, and future research tasks were discussed.